Pelatihan Pendamping PPH Halal Center UMsurabaya Untuk Mensukseskan Program Sertifikasi Halal Pemerintah - Anas Muhammad; Fitri Nuraini; Siti Mardiyah; Baterun Kunsah; Yeti Eka Sispita; Luluk Latifah; Nina Veronica; Ali Immanudin; Andre Ridho Saputro; Ridho Akbar; Agus Purwanto; Huliyyatul Wahdah; Ahmad Mochtar Jamil; Tiffany Lovenlya Indy Ayu Putri Kundayadi; Thariq Malikul Mulki; Nova Ulumiya; Wahyu Setiawan; Ridho Akbar (LPPM Universitas HKBP Nommensen, 2023)
Community service is carried out to welcome the obligatory halal food and beverage on October 17, 2024. Most micro and small businesses do not understand. The methods used are 1) exploring the understanding of halal certification, 2) conducting socialization of mandatory halal, 3) providing assistant staff for processing halal products by conducting training, and 4) assisting in registering self-declared halal certification through the Si Halal application. The results of community service activities provided 140 assistants in the process of halal products and issued halal certificates for food and beverage products owned by micro-small business actors in 91 certificates. Some obstacles are faced by unstable internet connection, the motivation of assistants and business actors fluctuate, the ability to operate gadgets is still limited, and many business actors do not have NPWP and NIB. As the obligation for halal certification is getting closer, it is necessary to socialize the obligation for halal certification more massively so that all business actors immediately take care of the halal certification of their products.